2010
DOI: 10.2500/ajra.2010.24.3522
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Attenuates Allergic Inflammation and Induces Production of Regulatory T Lymphocytes

Abstract: Given the potent effectiveness shown by PIO, we conclude that PPAR-gamma agonists deserve investigation as potential therapies for human allergic upper airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In summary, the present study has demonstrated that PPAR γ affects mouse mast cell progenitors by inhibiting granule formation and suppressing degranulation in response to FcεRI-antigen stimulation and that PPAR γ agonist attenuates BMMCs in vitro differentiation after systemic treatment and notably increases apoptosis. Consistent with our previous in vivo studies ( 7 , 21 ), PPAR γ agonists might have clinical potentials for allergic disorders, such as allergic rhinitis, asthma, and atopic dermatitis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In summary, the present study has demonstrated that PPAR γ affects mouse mast cell progenitors by inhibiting granule formation and suppressing degranulation in response to FcεRI-antigen stimulation and that PPAR γ agonist attenuates BMMCs in vitro differentiation after systemic treatment and notably increases apoptosis. Consistent with our previous in vivo studies ( 7 , 21 ), PPAR γ agonists might have clinical potentials for allergic disorders, such as allergic rhinitis, asthma, and atopic dermatitis.…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported that PPAR γ agonist attenuated allergic inflammation in a mouse model of allergic rhinitis ( 21 ). PIO is the effective agent in suppressing allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of pioglitazone was chosen based on published reports and modified as a result of results from our laboratory. 24, 25 …”
Section: Materials and Methods Or Experimental Proceduresmentioning
confidence: 99%
“…CD4 + Foxp3 + T regulatory cells (Tregs) are pivotal in the maintenance of self‐tolerance and immune homeostasis. They are known to exert therapeutic effects on autoimmune diseases, allergy, and allograft rejection in murine models and human patients . At least 2 subtypes of Tregs have been described: thymically derived natural Tregs (nTregs), and inducible Tregs (iTregs) generated peripherally from CD4 + CD25 − T effector cells (Teffs).…”
mentioning
confidence: 99%